Peran Ustadzah Dalam Melatih Santri Mengelola Emosi (Studi Kasus Di Tpa Madrasatul Qur'an Banda Aceh) - Barlinty Isbaaniyaa Baruza; Salami Mahmud (Syntax Idea)
In general, every individual experiences emotions in their daily lives, as emotions are part of human nature. There are various ways to express emotions, whether visibly or not. Good emotions are those that can be managed well. The focus of this study is on the management of emotions among students trained by female Islamic teachers. Emotions can lead someone towards either negative or positive directions, so managing emotions is crucial in life. This research aims to determine the role of female Islamic teachers in training students to manage their emotions at the Madrastul Qur’an Islamic School. The approach used in this research is qualitative. The data collection techniques include interviews, observations, and documentation. The results show that female Islamic teachers have several roles in training students to manage their emotions, such as providing support, motivation, identifying causes, building brotherhood/sisterhood, explaining consequences, redirecting attention towards positive aspects, providing stimuli, being fair educators, creating a good learning atmosphere, being good listeners, not demanding or forcing students, giving praise, and setting a good example.